Currículo, escola e comunidade: limites, desafios e possibilidades - Fernandes, Zizelda Lima (2009)
This dissertation presents the results of a research accomplished at a public school of Vitoria da Conquista (BA), with most students of a peripheral quarter of the city, branded by great social problems, as criminality and violence. In it, it has been searched to verify how curriculum and social-cultural context of the students relate themselves in the routine of a school that works with earlier series of elementary teaching. The research focus the curriculum, in order to mainly analyze how it relates in the school routine with the social questions (poverty, unemployment, criminality and violence), how these questions are treated in the prescribed curriculum and how they relate themselves in the curriculum in action. It has been chosen the case study with qualitative survey because such methodology used to contribute to a better understanding of the object. The researcher has chosen as main subjects of research the students of four classes, two of the Cycle I and two of the Cycle II, their parents, their teachers and the management team (principal, viceprincipal, pedagogical coordinator and a secretary). And this way, it has been search to analyze the uses of curriculum in the school routine, through the Proposta Curricular (Propose of Curriculum), Projeto Pedagógico (Pedagogical Projetc) and the Plano de Desenvolvimento Escolar (Developing Plan of the School), and also through the observations at the school, semi-structured interviews with teachers and managers, group dynamics with texts and interactive workshop with the students. The theoretical basis has included studies about public school, school curriculum and the neighborhood effect . The results point that to construct a curriculum articulated with the social-cultural context of the students is a great challenge and that the school practices are often distant from the social practices of the students. So, it has become clear that how important is to review the role of the school and the teacher in the school context, as well as the limits, possibilities and challenges between what one lives at the school and what one lives at the community. It is proper to rebound that the school has been outlining goals in order to rescue itself as a possible space , specially through projects constructed collectively, involving whole school community